Ciric Fixed Point Theorems in T- Orbitally Complete Spaces with n-quasi contraction - Powar, PL; Sahu, GRK; Pathak, Akhilesh (International Journal of Computer Sciences and Engineering, 2025)
Poom Kuman, [Poom Kuman , Nguyen van Dung, A generalization of Ciric Fixed Point theorems, Filomat 29:7 (2015), 1549-1556] has established the generalized version of the result by Ciric [ L. B. Ciric, A generalization of Banach’s contraction principle, Proc. Amer. Math. Soc. 45 (1974) 267-273.]. By considering the most general form of quasi-contraction viz. n-quasi contraction, the authors have established the existence of unique fixed point in T- orbitally complete spaces in this paper.